Microplastic ingestion and co-exposure to Nosema ceranae and flupyradifurone reduce the survival of honey bees (Apis mellifera L.) - Tiritelli, Rossella; Zavatta, Laura; Tadei, Rafaela [UNESP]; Mathias da Silva, Elaine Cristina; Sgolastra, Fabio; Cilia, Giovanni (Elsevier, 2024)
Bees are exposed to several threats, including pathogens (i.e. Nosema ceranae), pesticides and environmental contaminants. The new insecticide flupyradifurone, and the microplastics in the environment, have raised significant concerns on bee health. This study evaluated the simultaneous effects of microplastics, flupyradifurone, and N. ceranae on honey bee health, focusing on survival rates, N. ceranae replication, daily food consumption, and bee midgut histological alterations. Results showed a significant decrease in bee longevity across all treatments compared to the control, with the combination of flupyradifurone, microplastics, and N. ceranae having the most severe impact. Microplastics and flupyradifurone exposure also increased N. ceranae proliferation, especially in bees subjected to both stressors. Histological analysis revealed reduced regenerative cell nests in the midgut and changes in the nuclear matrix, indicating stress responses. Overall, the simultaneous presence of both biotic and abiotic stressors in nature can synergistically interact, leading to harmful effects on bees.
Keywords: Environmental contaminats; Lifespan; Microsporidia; Midgut; Pesticides